Issues in monetary policy : the relationship between money and the financial markets - Matthews, Kent.; Booth, P. (Philip), 1964- (Chichester, England : John Wiley, 2006)
This book discusses the current issues in monetary policy and the relationship between monetary policy and financial markets. Also included are the many issues related to the conduct of monetary policy that are not yet settled and which will soon come to the fore.
Includes bibliographical references and index.
nmn 11/06/13
Loans
Keywords: Monetary policy